Variability in hospital care. Pulmonary rehabilitation in Colombia (2014)
Objective: To describe variations in the management of pulmonary rehabilitation (PR) programs in patients with Chronic Obstructive Pulmonary Disease (COPD) by Colombian physiotherapists. Materials and method: We conducted a cross-sectional, observational study with 250 Colombian physiotherapists who routinely work with COPD patients from Colombia. A survey was made to identify variations in procedures, components, structure and characteristics of PR programs according to the «Guidelines for the physiotherapy management in patients with pulmonary disease with spontaneously breathing» published by British Thoracic Society Physiotherapy (BTS). Additionally, socio-demographic data were collected. Results: The response rate was 89.6% (n = 224). At the time of the survey, 92% of those surveied spent most of their time working in rehabilitation programs. Regarding variations in the clinical practice, the physiotherapists mainly answered «always perform» activities with low level of evidence (Grade C and D) such as diaphragmatic breathing techniques (48.7%), pursed-lip breathing during exercise (62.9%) and techniques of breath control (37.5%). A high percentage of professionals also included interventions with a higher degree of recommendation (Grade A) such as peripheral muscle training (42.9%), respiratory muscle training (52.2%), education or counseling disease (56.7%), use of intermittent positive pressure ventilation (31.7%), and application of oxygen (40.6%). Conclusions: The study confirms that there are important variations in therapeutic care components of the PR proposed by the BTS for patients with Chronic Obstructive Pulmonary Disease. © 2013 Asociación Española de Fisioterapeutas.